Penggunaan Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) Pada Pokok Bahasan Struktur Atom Untuk Meningkatkan Hasil Belajar Siswa Kelas X SMA Negeri 2 Palu - Fajaryanti, Desi Eka; Tiwow, Vanny M. A.; Rahman, Nurdin (Jurnal Akademika Kimia, 2014)
The purpose of this research was to investigate the students’ learning outcomes toward the use of cooperative learning model of Think Pair Share (TPS) on the topic of atomic structure to the tenth year students of SMA 2 Palu. The method used was an experimental research. The population was the tenth year students of SMA 2 Palu in the academic year of 2012/2013. The research used purposive sampling technique (based on the specific reason: the two classes have the same average scores of class). The sample consisted of 32 X-A students as the experimental class (Think Pair Share (TPS) technique) and 32 X-D students as the control class. The data collection was through test on atomic structure. The testing of research data used statistic analysis one tale t-test (right) by employing its prerequisite test of normality and homogeneity. The average score of the experimental class was 12.63 with the deviation standard of 2.82 and of the control class was 9.89 with the deviation standard of 2.70. Based on the hypothesis testing, it was found that tcounted value >ttable or 3.98 > 1.66 with degree of significance of 00.5 and degree of freedom = 62. The Ho was rejected. It is concluded that the learning outcome by using cooperative learning of Think Pair Share technique on the topic of nuclear structure is higher than that of the conventional technique.